Specter of Globalization: Marx, Gramsci and Disjointed Time. (1st December 2019) - Bina, Cyrus
Abstract : This paper aims to combine a critique of political economy with that of transnational polity in a unified theoretical foundation. It begins by (1) exploring the development of capitalism into stages, (2) showing that this should necessarily lead to globalization, and (3) validating that in the epoch of globalization no hierarchical interstate (hegemonic or not) political order may stand a chance for survival. These highly abstract theoretical queries, on the one hand, follow Karl Marx's critique of capitalism, and on the other hand obtain further theoretical and historical concretization in Antonio gramsci's hegemony, before their realization at observable levels via the rise and fall of the postwar Pax Americana (1945–1979). Marx's "conquest of mode of production" and gramsci's hegemony set the context for a synthetic approach to the rise and fall of American power. Finally, the force of globalization is the arbiter of time, despite the declining power syndrome, in this disjointed polity.